2022
DOI: 10.1038/s41598-022-26611-2
|View full text |Cite
|
Sign up to set email alerts
|

High capacity for a dietary specialist consumer population to cope with increasing cyanobacterial blooms

Abstract: We present a common-garden experiment to examine the amphipod Monoporeia affinis, a key deposit-feeder in the Baltic Sea, a low diversity system offering a good model for studying local adaptations. In the northern part of this system, the seasonal development of phytoplankton is characterized by a single diatom bloom (high nutritional quality), whereas in the south, the diatom bloom is followed by a cyanobacteria bloom (low nutritional quality) during summer. Therefore, the nutrient input to the benthic syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 71 publications
(105 reference statements)
0
1
0
Order By: Relevance
“…S6). Taking into account the reported lower δ 15 N values of the amphipods in BS compared to WGB (Ledesma et al, 2022), the observed differences in the niche size can imply both a less diverse food base and lower fractionation as a result of higher nitrogen-use efficiency, which would be expected in BS, where the nitrogen availability is lower than in the more eutrophied WGB. Such mechanisms were documented in fishes (Carter et al, 1998), with a direct routing of amino acids to protein synthesis, resulting in the decrease of depleted nitrogen in urea and ammonia relative to the assimilation of nitrogen into the tissues, and a decreased tissue-diet enrichment.…”
Section: Variability Of the Measured Parametersmentioning
confidence: 90%
“…S6). Taking into account the reported lower δ 15 N values of the amphipods in BS compared to WGB (Ledesma et al, 2022), the observed differences in the niche size can imply both a less diverse food base and lower fractionation as a result of higher nitrogen-use efficiency, which would be expected in BS, where the nitrogen availability is lower than in the more eutrophied WGB. Such mechanisms were documented in fishes (Carter et al, 1998), with a direct routing of amino acids to protein synthesis, resulting in the decrease of depleted nitrogen in urea and ammonia relative to the assimilation of nitrogen into the tissues, and a decreased tissue-diet enrichment.…”
Section: Variability Of the Measured Parametersmentioning
confidence: 90%